Reconstruction of The Context of Coping with Occupational Stress Experienced by Specialists of Social Welfare Professions in Socially and Culturally Diverse Environment - Alifanovienė, Daiva; Šapelytė, Odeta; Gerulaitis, Darius (Social Welfare: Interdisciplinary Approach, 2018)
The article deals with the reconstruction of the context of coping with occupational stress experienced by social welfare specialists in different socio-cultural environments. It is aimed to reveal the contexts of the possibilities to cope with stress and of consequences of stress experienced by specialists of social welfare professions of Lithuania and Great Britain (N=10). The professionals’ experience was analysed using a qualitative data collection method (semi-structured interview), employing open-ended questions by the assessment areas foreseen by the researchers and formulated upon the analysis of scientific literature and the authors’ research, disclosing the peculiarities of experienced occupational stress and possibilities of coping with it. The research data were analysed employing the content analysis method, using the open coding procedure; validation of the research data was performed using an expert method. Reconstruction of the multilayered context of socio-cultural diversity of social welfare specialists of Lithuanian and Great Britain highlighted ambiguous semantics of stress coping possibilities: the success of coping with occupational stress possibly depends on the interaction between the variables of a personality (intrapersonal) and social environment (interpersonal). Stressful situations affect both personally and professionally, causing changes in specialists’ emotions, cognitive activity, behaviour, aggravating relationships with colleagues and reducing work efficiency.